Syair-syair karya Abu Tamam - Anggraini, Novia Retnowati (Maliki Interdisciplinary Journal, 2023)
Abu Tamam was a famous poet during the time of the Abbasid Daula, precisely during the leadership of al-Mu’tashim. He is known as a poet who is proficient in various fields of science, especially in the fields of history, theology, philosophy and logic. His extraordinary poetry proves that his imagination and contemplation are so wide. Abu Tamam also often combines aspects of philosophy and logic in his poetry. This research uses descriptive qualitative method through library research. Primary data comes from Syauqi Dhaif’s book entitled Tarikh al-Adab al-Araby fii al-’Ashri al-’Abbas al-Awwal as the main reference source. The secondary data comes from various references in accordance with the discussion under study. This research examines the collection of poems by Abu Tamam and the position of the poets among the leaders at that time.